ISLAMIC PERSPECTIVE ON TOURISM AND ITS BENEFITS - Firdaus Firdaus; Desmadi Saharuddin; Ilda Hayati (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
Tourism has enormous benefits in Islam and even has a positive impact on One's faith. Tourism is a part of "maqashid" shari'a, which consists of preserving religion, soul, reason, descent (honor), and property. Tourism can even be covering all of these aspects of this "maqashid" because it is supported by the texts of the Qur'an and the Hadith, which show the virtues and benefits of the tour. By conducting a literature study, verifying data, and interpreting the Author using a descriptive analysis approach, it was found that tourism is a part of being related to all aspects of sharia maqashid, which have been done by previous peoples. Islam recommends pilgrimages to three places, namely Haram Mosque, Nabawi Mosque, and Aqsa Mosque. Islam also has signs in travel for Muslims and also for non-Muslims who enter Muslim territory. Non-Muslims come to Muslim countries not to commit immoral acts like those done in their countries. Still, they want to enjoy the beauty of nature and know the culture that exists so that Muslims do not need to provide facilities that are prohibited in Islam to support tourism.